Application of SEM/EDS in Fractographic Investigation of TIG Welded AISI 1020 Fusion Zones at Distinct Welding Current Steps - Owunna, I. B.; Ikpe, A. E.; Ohwoekevwo, J. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Higher arc length is a function of increasing welding current (amperage). It increases the intensity of welding heat, thereby, influencing the microstructure and mechanical properties of the welded material. In this this study, fractographical variations in TIG welded AISI 1020 fusion zones at different welding current steps were investigated using Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM/EDS) techniques. The fracture morphologies showed a fibrous appearance indicating ductile fracture with initiation of a river pattern of branching cracks, forming cleavages along the crystals plains and intergranular fracture occurring along the grain boundaries, indicating brittle fracture as a result of stepwise increase in welding current. It was observed that the ultimate tensile strength of the welded samples decreased correspondingly from 583.3 MPa, 540 MPa, 530.7 MPa, 506.7 MPa to 473.3 MPa as the resulting heat input due to welding current increased from 96.14 A, 120 A, 155 A, 190 A to 213 A. This indicated that the lowest welding current (96.14A) produced fusion zone with the highest ductility when compared to other welding currents which produced fusion zones that tended to be brittle as a result of increasing heat inputs. It was observed that fusion zone with the lowest welding current showed the appearance of a fibrous structure produced by stretching of crystals in their lattice during heat application. Micro-hardness on the surface of the welds revealed that hardness increased with increase in welding current. Therefore, proper control measures should be put in place to ensure that welding input parameters are optimum.